The pocket ball-room prompter, containing calls for the different changes and figures to all the principal quadrilles, cotillons, country dances and fancy dances of the day ... - Howe, Elias, 1820-1895.; Miniature Book Collection (Library of Congress) (Boston, O. Ditson & Co., 1886)
This small, pocketsize manual is attributed to American inventor Elias Howe; however, a publisher assembled it. Even though the manual itself is small in size, it manages to pack in a thorough discussion of etiquette of the ballroom and supper room, the differences between public balls and private parties, and how to call quadrilles or cotillons. Descriptions are included for numerous dances including the polka, waltz, schottisch, quadrille, and contra dance.
Available also through the Library of Congress Web site as facsimile page images and full text.
Keywords: Ballroom dancing -- Handbooks, manuals, etc; Dance Instruction and Technical Manuals